2016
DOI: 10.1080/17441692.2015.1134272
|View full text |Cite
|
Sign up to set email alerts
|

From MSM to heteroflexibilities: Non-exclusive straight male identities and their implications for HIV prevention and health promotion

Abstract: This article examines the logics of self-identification among men who have same-sex desires and behaviours and consider themselves to be straight. We draw from interviews conducted in the USA with 100 straight-identified men who have same-sex desires and 40 partners of such men. Our data allow us to reject two misconceptions. One is the idea that these men are actually gay or bisexual but refuse to accept those identities. We argue instead that these men see themselves as straight and therefore it is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…Rather, it may be that these men, like the participants in Carrillo and Hoffman's recent qualitative study of 100 heterosexual-identifying MSM in the USA, firmly identify with a heterosexual identity, do not wish to be seen otherwise and do not see their self-identities changing; it may be that they see themselves as 'heteroflexible' with 'elastic sexualities'. 27 Of note, Carrillo's study sample was not limited to Latinos but included other races (ie, White, African American, Native American, Asian American and Middle Eastern/ White) which may extend the relevance of the present study beyond heterosexually identified Peruvian MSM.…”
Section: Discussionmentioning
confidence: 97%
“…Rather, it may be that these men, like the participants in Carrillo and Hoffman's recent qualitative study of 100 heterosexual-identifying MSM in the USA, firmly identify with a heterosexual identity, do not wish to be seen otherwise and do not see their self-identities changing; it may be that they see themselves as 'heteroflexible' with 'elastic sexualities'. 27 Of note, Carrillo's study sample was not limited to Latinos but included other races (ie, White, African American, Native American, Asian American and Middle Eastern/ White) which may extend the relevance of the present study beyond heterosexually identified Peruvian MSM.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to what Schnarr et al’s (2012) found, some participants felt that receptive anal sex with a man was an opportunity to explore their feminine, weaker, or softer side (although this was distinct from being “effeminate,” or feminine in self-presentation). Carrillo and Hoffman (2016) also found that heterosexually-identified men sought out sex with men when needing a relief from the expectation of always being in control in their relationships with women or, “a respite from the burdens of hegemonic forms of masculinity” (p. 931). Indeed, some of our participants were dissatisfied with having to perform the traditional masculine role in their relationships with women.…”
Section: Discussionmentioning
confidence: 99%
“…This group of men (often described in popular media as men “on the down-low”) has received much attention from sex researchers because they represent a potential “bridge population” that could acquire HIV and other sexually transmitted infections (STIs) from their male partners and transmit these infections to their female partners (Doll & Beeker, 1996; Ekstrand et al, 1994; O’Leary & Jones, 2006). Several studies have investigated why these men choose to not disclose their same-sex behavior (Benoit & Koken, 2012; Malebranche, Arriola, Jenkins, Dauria, & Patel, 2010; Schrimshaw, Downing, & Cohn, 2018; Schrimshaw, Downing, Cohn, & Siegel, 2014; Schrimshaw, Siegel, Downing, & Parsons, 2013) and why many of them continue to regard themselves as heterosexual despite their homosexual behaviors (Baldwin et al, 2015; Carrillo & Hoffman, 2016; Persson et al, 2017; Reback & Larkins, 2010; Ward, 2015). Yet, researchers have not paid much attention to similarities or differences in how these men perceive their sexual and intimate relations with men and women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations